Modeling the polarization of high-energy radiation from accreting black holes : A case study of XTE J1118+480 - Vieyro, Florencia Laura (2016)
Context. The high-energy emission (400 keV-2 MeV) of Cygnus X-1, which is the best-studied Galactic black hole, was recently found to be strongly polarized. The origin of this radiation is still unknown. Aims. We suggest that the emission is the result of non-thermal processes in the hot corona around the accreting compact object and study the polarization of high-energy radiation that is expected for black hole binaries. Methods. Two contributions to the total magnetic field were taken into account in our study: a small-scale random component related to the corona, and an ordered magnetic field associated with the accretion disk. The degree of polarization of gamma-ray emission for this particular geometry was estimated together with the angle of the polarization vector. Results. We obtain that the configuration of corona plus disk can account for the high degree of polarization of gamma-rays that are detected in galactic black holes and does not need to invoke a relativistic jet. We make specific predictions for sources in a low-hard state. In particular, the model is applied to the transient source XTE J1118+480. We show that if a new outburst of XTE J1118+480 is observed, then its gamma-ray polarization should be measurable by future instruments, such as ASTRO-H or the proposed ASTROGAM.